A data-driven global innovation system approach and the rise of China's artificial intelligence industry. Issue 4 (3rd April 2022) - Yu, Zhen; Liang, Zheng; Xue, Lan
ABSTRACT: Building upon the global innovation system (GIS) framework, this paper develops an analytical approach to incorporate data as a foundation-level resource in data-driven innovation systems and to unravel how the interplay of system resources' spatial characteristics, multi-scalar institutions and actor strategies leads to the emergence of China's artificial intelligence industry. China's loose institutional regime significantly facilitates the formation of the market, legitimacy and data, while entrepreneurs and digital platforms are the key actors coupling system resources to China's innovation system. As data become a critical resource, actors controlling data develop institutional power to shape the formation of the data-driven industry.